Sensitivity of trading intensity to optimistic and pessimistic beliefs: Evidence from the French stock market - Abderrazak Dhaoui; Naceur Khraief (Arab Economic and Business Journal, 2014)
In this paper, we will offer some evidence indicating that investor sentiment plays a central role in explaining trading intensity and market trend changes. Based on both econometric and fuzzy logic approaches, the empirical findings show that pessimistic sentiment has a particularly significant impact on the French financial market trend. Moreover, the results suggest that the impact of pessimism on asset returns exceeds that of optimism as a direct indicator of investor's beliefs. Indirect indicators of agent sentiment present more smoothed effects on these two market components. Our results indicate that incorporating psychological factors in macro-financial models leads to better supervision and control of the main drivers of the markets.
Keywords: 650; Trading intensity; Market trend; Animal spirits; Fuzzy logic